(3GdeDJda hGdeNJdas - (3GdOQGbWfj , CHh GdMSf,J (B385 (3g` s
(3ChdgG (B:s
(3jHOC ef HGH (B: (3RjGO hRfGO hRHGO s
(3BNQgG (B:s
(3hjfJgi HBNQ GdcJGH s
(3ef fSNI fajSI YdjgG SeGYGJ eNJdaI HYVgG eDQN SfI (B612(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B157s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B164 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1637s
(3eUOQ GbJfGA GdCUd (B:s
(3eOjfI (B(414) s
Keywords: (3GdJGQjNs